2017
DOI: 10.1101/108845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitroinduction andin vivoengraftment of lung bud tip progenitor cells derived from human pluripotent stem cells

Abstract: SummaryThe bud tip epithelium of the branching mouse and human lung contains multipotent progenitors that are able to self-renew and give rise to all mature lung epithelial cell types. The current study aimed to understand the developmental signaling cues that regulate bud tip progenitor cells in the human fetal lung, which are present during branching morphogenesis, and to use this information to induce a bud tip progenitor-like population from human pluripotent stem cells (hPSCs) in vitro. We identified that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 87 publications
(176 reference statements)
0
44
1
Order By: Relevance
“…In the present study, we reconstructed human airway epithelium-like structure in vivo by using hESCs-derived lung organoid cells. Compared with the previous report that hPSC-derived epithelial bud tip organoid cells could form patch structures along the airway epithelium [6], in our study, engrafted hESCsderived lung organoid cells could survival, differentiate and long-term reconstruct airway epithelium-like structure. It has been reported that CD47 high cells were NKX2.1+ cells [8], and our RNA-seq data indicated that CD47 high cells in D25 lung organoids were lung lineage determined cells.…”
contrasting
confidence: 64%
See 3 more Smart Citations
“…In the present study, we reconstructed human airway epithelium-like structure in vivo by using hESCs-derived lung organoid cells. Compared with the previous report that hPSC-derived epithelial bud tip organoid cells could form patch structures along the airway epithelium [6], in our study, engrafted hESCsderived lung organoid cells could survival, differentiate and long-term reconstruct airway epithelium-like structure. It has been reported that CD47 high cells were NKX2.1+ cells [8], and our RNA-seq data indicated that CD47 high cells in D25 lung organoids were lung lineage determined cells.…”
contrasting
confidence: 64%
“…Immune deficient B-NSG (NOD-Prkdcscid IL2rgtm1/Bcgen) mice were purchased from Beijing Biocytogen Co., Ltd. (Beijing, China). Naphthalene (NA) (200mg/ml) was intraperitoneal injected once as previous described [6].…”
Section: Naphthalene-induced Lung Injury Mice Model and Cell Transplamentioning
confidence: 99%
See 2 more Smart Citations
“…There are more than 20 different genetic mutations that have been described in nonsyndromic CDH, and a laboratory gene panel does not currently exist to screen for these genes 10 . Third, it is possible that alternative directed differentiation protocols, as we and others have described, 85‐87 may yield different results within our ex vivo compression system. Fourth, unlike hypoplastic fetal rodent lung explants used in our laboratory and elsewhere, 73 this organoid model is not suitable for studying aberrant CDH branching morphogenesis 86 and the subsequent instructional role that airway smooth muscle may play during this process 88 .…”
Section: Discussionmentioning
confidence: 99%